Synthesis and properties of some S-derivatives of 4-phenyl-5-((5- phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione - Hotsulia, А. S.; Fedotov, S. O.; Гоцуля, Андрій Сергійович; Федотов, С. О.; Гоцуля, А. С. (Запорізький державний медичний університет, 2019)
Studies in the field of chemistry and pharmacology of derivatives of thiadiazole and 1,2,4-triazole are promising and relevant, which is associated with significant success in creating new drugs based on them. The combination of these heterocycles in one molecule makes it possible to increase the probability of detecting substances with a certain type of biological activity among the synthesized compounds. The aim of the work was to optimize the synthesis and study of the properties of S-alkyl derivatives of 5-R-4-phenyl-1,2,4-triazole-3- thione, containing a thiadiazole fragment in their structure, as well as the prediction of possible biological activity to rating the prospects of further studies in vivo and in vitro. Materials and methods. As a key starting reagent, 3-amino-1-phenylthiourea was used. Using the reaction between the starting reagent and carbon disulfide in DMF, thion was obtained, which was further alkylated with isopropyl chloroacetate. The resulting reaction product was then used for subsequent transformations using hydrazinolysis reactions, nucleophilic addition of phenylisothiocyanate and intramolecular alkaline heterocyclization. A number of S-derivatives of the obtained 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole- 2-ylthio)methyl)-1,2,4-triazole-3-thione were synthesized by the interaction with haloalkanes in the presence of an equivalent amount of alkali in alcoholic medium. The structure of the obtained compounds was confirmed by elemental analysis, 1H NMR spectroscopy, and IR-spectrophotometry. The individuality of substances was established by high performance liquid chromatography. For the synthesized substances, an individual calculated screening was performed using the PASS Online® software product. Results. The procedure for preparing 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione was optimized. The optimal synthesis conditions were determined S-alkylderivatives of 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)- 1,2,4-triazole-3-thiol, the structure was established the obtained substances and their physical properties were studied. With the help of computer-assisted prediction Pass Online®, a promising direction for further studies of the biological activity of the target reaction products was determined. Conclusions. A series of S-alkylderivatives of 4-phenyl-5-((5-phenylamino-1,3,4-thiadiazole-2-ylthio)methyl)-1,2,4-triazole-3-thione were obtained, the structure of these compounds was confirmed by physical-chemical methods of analysis. At the next stages of the study, it would be planned to establish indicators of the antimicrobial activity of the synthesized substances. лими успіхами створення нових лікарських засобів на їхній основі. Поєднання цих гетероциклів в одній молекулі дає можливість підвищити ймовірність виявлення серед синтезованих сполук речовин із певним видом біологічної активності. Мета роботи – оптимізація умов синтезу та дослідження властивостей S-алкілпохідних 5-R-4-феніл-1,2,4-тріазол-3-тіону, що містять у своїй структурі тіадіазольний фрагмент, а також прогнозування можливої біологічної активності для оцінювання перспективності дальших досліджень in vivo та in vitro. Матеріали та методи. Як ключовий вихідний реагент використали 3-аміно-1-фенілсечовину. За допомогою реакції взаємодії вихідного реагенту з карбон дисульфідом у середовищі ДМФА отримали тіон, який надалі проалкілований ізопропіловим естером кислоти хлороетанової. Продукт реакції використали для дальших перетворень із використанням реакцій гідразинолізу, нуклеофільного приєднання фенілізотіоціанату та внутрішньомолекулярної лужної гетероциклізації. Ряд S-похідних одержаного 4-феніл-5-((5-феніламіно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону синтезували взаємодією з галогеналканами за наявності еквівалентної кількості лугу у спиртовому середовищі. Структура отриманих сполук підтверджена даними елементного аналізу, 1Н ЯМР-спектроскопії та ІЧ-спектрофотометрії. Індивідуальність речовин встановлена за допомогою високоефективної рідинної хроматографії. Для синтезованих речовин здійснили індивідуальний розрахунковий скринінґ за допомогою програмного продукту PASS On-line®. Результати. Оптимізували методику отримання 4-феніл-5-((5-феніламіно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону. Визначили оптимальні умови синтезу S-алкілпохідних 4-феніл-5-((5-феніламіно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону, встановили будову отриманих речовин і дослідили їхні фізичні властивості. За допомогою комп’ютерного прогнозування PASS On-line® визначили перспективний напрям наступних досліджень біологічної активності цільових продуктів реакції. Висновки. Синтезували ряд S-алкілпохідних 4-феніл-5-((5-феніламіно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону, структура яких підтверджена фізико-хімічними методами аналізу. На наступних етапах досліджень планується встановлення показників антимікробної активності синтезованих речовин. Исследования в области химии и фармакологии производных тиадиазола и 1,2,4-триазола являются перспективными и актуальными, что связано со значительными успехами создания на их основе новых лекарственных средств. Сочетание данных гетероциклов в одной молекуле позволяет повысить вероятность обнаружения среди синтезированных соединений веществ с определенным видом биологической активности. Цель работы – оптимизация условий синтеза и исследования свойств S-алкилпроизводных 5-R-4-фенил-1,2,4-триазол-3-тиона, содержащих в своей структуре тиадиазольный фрагмент, а также прогнозирование возможной биологической активности для оценки перспективности дальнейших исследований in vivo и in vitro. Материалы и методы. В качестве ключевого исходного реагента использована 3-амино-1-фенилмочевина. С помощью реакции взаимодействия исходного реагента с карбон дисульфидом в среде ДМФА получен тион, который в дальнейшем проалкилирован изопропиловым эстером кислоты хлороэтановой. Полученный продукт реакции использован для последующих превращений с использованием реакций гидразинолиза, нуклеофильного присоединения фенилизотиоцианата и внутримолекулярной щелочной гетероциклизации. Ряд S-производных полученного 4-фенил-5-((5-фениламино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона синтезирован взаимодействием с галогеналканами в присутствии эквивалентного количества щелочи в спиртовой среде. Структура полученных соединений подтверждена данными элементного анализа, 1Н ЯМР-спектроскопии и ИК-спектрофотометрии. Индивидуальность веществ установлена с помощью высокоэффективной жидкостной хроматографии. Для синтезированных веществ проведен индивидуальный расчетный скрининг с помощью программного продукта PASS On-line®. Результаты. Оптимизирована методика получения 4-фенил-5-((5-(фениламино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона. Определены оптимальные условия синтеза S-алкилпроизводных 4-фенил-5-((5-(фениламино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона, установлено строение полученных веществ и исследованы их физические свойства. С помощью компьютерного прогнозирования Pass Online® определено перспективное направление дальнейших исследований биологической активности целевых продуктов реакции. Выводы. Синтезирован ряд S-алкилпроизводных 4-фенил-5-((5-(фениламино-1,3,4-тиадиазол-2-илтио)метил)-1,2,4-триазол-3-тиона, структура которых подтверждена физико-химическими методами анализа. На последующих этапах исследований планируется установление показателей антимикробной активности синтезированных веществ.
Синтез і властивості деяких S-похідних 4-феніл-5-((5-феніламіно-1,3,4-тіадіазол-2-ілтіо)метил)-1,2,4-тріазол-3-тіону
Синтез и свойства некоторых S-производных 4-фенил-5-((5-фениламино-1,3,4-тиадиазол-2-илтио)метил)- 1,2,4-триазол-3-тиона
Keywords: thiadiazole; 1,2,4-triazole; physical-chemical properties; screening studies; тіадіазол; 1,2,4-тріазол; фізико-хімічні властивості; прескринінґові дослідження; тиадиазол; 1,2,4-триазол; физико-химические свойства; прескрининговые исследования